KEPEMIMPINAN PROFETIK DI LEMBAGA PENDIDIKAN PONDOK PESANTREN: Studi Kepemimpinan Profetik K.H. Adib Amrullah di Pondok Pesantren Darussa’adah, Bulus-Kritig, Petanahan, Kebumen - Muhtadi, Farid (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2018)
Kiai is seen as a very influential figure in pesantren life. In addition to the charismatic figure, whatever is taught by a kiai is seen as an absolute truth that can not be "inviolable". The charisma of a kiai in pesantren makes the kiai very respected and respected by the ustadz and santrinya. The continuity of a pesantren depends on a kiai as its leader. For that a kiai is a person who must have the ability so that it can run its role as leader of the pesantren. Speaking of the role of kiai in leadership, it will not be separated from the task of kiai in managing and doing supervision (control) in pesantren. So it is natural that the growth and development of a pesantren depends on the personal leadership ability of the kiai. Pesantren management is very dependent on Kiai. In pesantren the highest authority is absolute in the hands of the pesantren nurse. Kiai as the spirit of pesantren, its vital role can not be replaced by other components. Therefore, it can be said that the life of a pesantren is very dependent on Kiai.Key Words: Leadership, Kyai and Pesantren